Sealing of oil-gas reservoir caprock: Destruction of shale caprock by micro-fractures - Tao, Ye; He, Youbin; Zhao, Zhongxiang; Wu, Dongsheng; Deng, Qiao (Frontiers in Earth Science, 2023)
The sealing ability of caprock is affected by many factors, such as cap thickness, displacement pressure, fracture development, and lithology of caprock. Shale is one of the ideal materials for oil and gas sealing cap formation due to its low porosity and permeability. Microfractures can destroy the sealing property of shale caprock. When buried deep enough, shale will change from toughness to brittleness. In general, the greater the brittleness of shale, the more developed the fractures will be. In areas with high tectonic stress, such as the anticline axis, syncline axis and stratum dip end, the strata stress is high and concentrated, and it is easier to generate fractures. When the stress state of the caprock changes, new micro-cracks are formed or previously closed cracks are re-opened, reducing the displacement pressure of the caprock. These micro-fractures are interconnected to form microleakage spaces, which reduces the sealing capacity of the caprock.